Late Prehispanic occupations in the upper basin of the Mala river, Sangallaya, Huarochirí - Aguirre Morales Prouve, Manuel Augusto (2023)
In 2017, the Archaeological Research Project "Excavations of three late settlements: Llipaya, Mitolaya and Sinquiranchi, in Sangallaya, high valley of Mala, Huarochirí, Lima" was carried out. In this first stage, the studies had the objective of identifying the archaeological sites present in this sector of the valley and the activities of the social, political and economic organization of the populations settled during the late periods in the zone of the upper valley of Mala, defining the main economic activities developed by the population in the three mentioned archaeological sites. The works began with the prospecting of the area, these resulted in the recognition of the archaeological sites studied; likewise, archaeological excavations were carried out; and finally, the material was analyzed. Based on the architectural distribution and the material recovered during the excavations, the articulation of the three archaeological settlements during the Intermediate and Late Horizon is inferred.